Storying teacher education policy: Critical counternarratives of curricular, pedagogical, and activist responses to state-mandated teacher performance assessments - Henning, Nick; Dover, Alison G.; Dotson, Erica K.; Agarwal-Rangnath, Ruchi (Education Policy Analysis Archives, 2018)
The rise of high-stakes, standardized, teacher performance assessments (TPAs) is central to the industry being created out of the regulation, policing, and evaluation of university-based teacher education In addition to reinforcing a narrow and counter-critical framework, TPAs can shift responsibility for the evaluation of teacher candidates from university-based teacher educators with a comprehensive and nuanced fluency in candidates' preparedness to external scorers trained to standardize and depersonalize effective practice. In this article, four social justice-oriented teacher educators from three different states examine the practical and political effects of TPAs in their local contexts. By analyzing the curricular, pedagogical, and political implications of this high-stakes standardization of their field, they speak back to a policy landscape that too often marginalizes the voices of the teachers and students it purports to serve. Throughout, they examine the dilemmas of practice created by TPAs, as teachers and teacher educators seek to redefine what it means to enact justice-oriented professional agency in an increasingly regulated context. A critical counternarrative methodological approach was used to collect and process the authors’ lived stories and then to collaboratively reflect upon each other’s personal/professional experiences with TPAs. Several strategies are identified for enacting agency in response to TPAs, including curricular acts of resistance, resistance through participation in state legislative processes, policymaking within teacher education programs, the production of activist scholarship, and refusal to participate at all. Ways are suggested for teacher educators to minimize, mitigate, and resist unjust policy through curricular, political, and scholarly activism.